Reviewing and comparing the impact of aerobic exercise (3 and 5 times per week) on insulin receptors, glucose transporter protein (GLUT4), and skeletal muscle insulin sensitivity in diabetic rats - Mohammad Reza Yousefia, Salar Bakhtiyarib, Ahmad Valizadehc (Journal of Applied Pharmaceutical Science, 2017)
Objectives: The diabetes is a metabolic disease which is caused by chronic disease of blood glucose due to low insulin secretion, insulin resistance, or both of them. The sports activities have a major impact on prevention, treatment, and reduction of diabetes effects. Therefore, this study aimed to review and compare the impact of aerobic exercise (3 and 5 times per week) on some factors which are involved in glucose transition to skeletal muscles of diabetic rats.Materials & Methods: A total of 30 Wistar rats were divided into three groups: diabetic, control (n=8); exercise group, 3 times a week (n=11); and exercise group, 5 times a week (n=11). The exercise groups ran on treadmill for 6 weeks with progressive intensity and duration. The variance analysis test was used to detect the significance of difference between groups. Also, the paired t-test was used to evaluate changes of groups in pre-test and post-test.Results: The findings showed that the insulin sensitivity and insulin receptor levels increased significantly in aerobic exercise groups (3 and 5 times a week) compared to control group (p
Keywords: Aerobic Exercise, Insulin Receptors, Glucose Transporter Protein (GLUT4), Insulin Sensitivity.